MAPPING POTENTIAL AREAS TO GENERATE PHOTOVOLTAIC ENERGY IN SANTA CATARINA’S STATE - Simoni Schuch, Fernanda; Souza Averlan, Murilo; Krueger da Silva, Fábio; João da Silveira, Samuel (Journal of Interdisciplinary Debates, 2021)
The need for diversification of the world’s electricity matrix has led to an increase in the demand for energy production with a focus on reducing environmental impacts. With the intensification of investments and incentives in the development of innovative projects for energy generation, from renewable sources, it was verified the occurrence of benefits from both the electric, socioeconomic and environmental point of view. This research has as main focus the application of Geographic Information Systems (GIS) in conjunction with the multicriterial Evaluation Analytic Hierarchy Process (AHP), aiming to define the most favorable areas for installation of systems of electric power generation through solar energy photovoltaic, with the state of Santa Catarina being the object of study. A set of criterias were defined regarding the implementation of solar power plants, such as: the availability of the existing solar radiation in the area, the distance of electric power transmission lines, distance from streets, distances from urbanized areas, the declivity of the area, the existence of conservation units, the hydrography and, land use and occupation. Afther that, it was possible to perform analysis and considerations on the highlighted areas, with greater aptitude to build solar energy plants, verifying if the adopted criterias provided a coherent result due to the geographic, occupational and solar irradiance characteristics of Santa Catarina State. It was also possible to quantify the areas identified as more proper, by presenting them on a solar photovoltaic potential map and also, to estimate its total solar energy potential.